Exercise for Dysphagia Pasca Stroke : A Literature Review - Annisa Fitri Dewi; Umi Budi Rahayu; Subandi (Universitas Negeri Semarang, 2025)
Stroke causes many complications, one of which is dysphagia which is common after a stroke. Medical complications of dysphagia include the risk of aspiration pneumonia which results in increased hospitalization and morbidity. Several approaches to treating dysphagia can be taken including exercise therapy interventions. The aim of this study was to examine the effects of exercise for stroke patients with dysphagia. The method of this research was to look for studies related to exercise in post-stroke dysphagia and review them using an electronic database. Search for articles to review using the keywords “exercise”, “dysphagia”, and “stroke” and their combinations. The results of data extraction found a total of five pieces of literature which were thoroughly reviewed in the form of resistance training combined with kinesiology taping, group-based training, lingual strengthening exercise, Inspiratory and Expiratory Respiratory Muscle Training (IEMT), and McNeill Dysphagia Therapy Program (MDTP) exercises, showing that training for post-stroke dysphagia not only improves swallowing ability but can also improve mood, quality of life, and swallowing efficiency and reduce the cost of post-stroke dysphagia treatment. The conclusion of the review study was that in general exercise can overcome post-stroke dysphagia.